Assimilation, Reduction and Elision Reflected in the Selected Song Lyrics of Avenged Sevenfold - Dwi Nita Febriyanti (Journal of Language and Literature, 2015)
This paper discusses the phenomena of phonological rules, especially assimilation, reduction and elision processes. In this paper, the writer conducted phonological study which attempts to find the phenomena of those processes in song lyrics. In taking the data, the writer transcribed the lyrics of the songs, along with checking them to the internet source, then observed the lyrics to find the phenomena of assimilation, reduction, and elision. After that, she classified the observed phenomena in the lyrics based on the phonological processes. From the data analysis, the results showed that there were three processes found both in the first and second songs: assimilation, reduction and elision. The difference is that in the first song, it has four kinds of assimilation, while from the second song only has three kinds of assimilation.Keywords: assimilation, reduction, elision